PERBANDINGAN NILAI AGREGASI TROMBOSIT PADA PASIEN DIABETES MELITUS TIPE 2 DENGAN DISLIPIDEMIA DAN NORMOLIPIDEMIA DI RSUP PROF. DR. R. D. KANDOU MANADO - Sulamanda, Ivan Ch. (eBiomedik, 2014)
Abstract: Insulin resistance that occurs in patients with type 2 diabetes mellitus (T2DM), stimulates lipolysis in adipose tissue resulting in increasing of free fatty acid and dyslipidemia. Dyslipidemia is associated with platelet reactivity and thrombogenic potency. Examination of platelet aggregation aims to detect abnormalities of platelet function. This study aimed to obtain the comparison of platelet aggregation values in T2DM patients with dyslipidemia and with normal blood lipid level. This was an observational analytical study, using comparative hypothesis test. This study were conducted on 30 T2DM patients, in which 15 of them have dyslipidemia and the other 15 has normal lipid level. These patients were registered as outpatients of Endocrine and Metabolic Clinic of Prof. Dr. R. D. Kandou Hospital, Manado. Blood samples of patients were processed in Prokita Laboratory, Manado. Platelet aggregation was tested by using 1 set agregometer Chrono - Log model 490, Chrono - Log recorder model 707, and Computer Windows based PC. The T test showed that there were significant differences of the platelet aggregation values with ADP 10 µm agonist between T2DM patients with dyslipidemia and with normal blood lipid level (P = 0.019). Mann-Whitney test showed that there were significant differences of the platelet aggregation values with ADP 5 µm agonist between T2DM patients with dyslipidemia and with normal blood lipid level (P = 0.006). Most patients in this study were elderly (86.7%), with an equal number of men and women. Conclusion: There were significant differences of the platelet aggregation values between T2DM patients with dyslipidemia and with normal blood lipid level, whether using ADP 10 µm agonist or ADP 5 µm agonist. Keywords: platelet aggregation, T2DM, dyslipidemiaAbstrak: Pada pasien diabetes melitus tipe 2 (DMT2), resistensi insulin merangsang lipolisis di jaringan adiposa yang meningkatkan asam lemak bebas sehingga terjadi dislipidemia. Dislipidemia sering dikaitkan dengan peningkatan aktivitas platelet dan potensi trombogenik. Pemeriksaan agregasi trombosit bertujuan untuk mendeteksi abnormalitas fungsi trombosit. Penelitian ini bertujuan untuk melihat perbandingan nilai agregasi trombosit pada pasien DMT2 dengan dislipidemia dan normolipidemia. Penelitian ini bersifat observasional analitik dengan menggunakan metode uji hipotesis komparatif. Subjek penelitian berjumlah 30 orang, terdiri dari 15 pasien DMT2 dengan dislipidemia dan 15 pasien DMT2 dengan normolipidemia yang berobat ke Poliklinik Endokrin Metabolik RSUP Prof. Dr. R. D. Kandou Manado. Pemeriksaan sampel darah pasien dilakukan di Laboratorium Prokita Manado. Pemeriksaan agregasi trombosit menggunakan 1 set agregometer Chrono - Log model 490, Chrono - Log recorder model 707, Computer Windows based PC. Karakteristik terbanyak pada pasien DMT2 terdapat pada usia tua (86,7%) dengan jenis kelamin laki - laki dan perempuan sama banyak (50%). Hasil uji T menunjukkan terdapat perbedaan bermakna antara nilai agregasi trombosit menggunakan agonis ADP 10 µm pada pasien DMT2 dengan dislipidemia dan normolipidemia (P = 0,019). Uji Mann-Whitney juga menunjukkan terdapat perbedaan bermakna antara nilai agregasi trombosit dengan agonis ADP 5 µm pada pasien DMT2 dengan dislipidemia dan normolipidemia (P = 0,006). Simpulan: Terdapat perbedaan bermakna antara nilai agregasi trombosit pada pasien DMT2 dengan dislipidemia dan normolipidemia baik menggunakan agonis ADP 10 µm maupun ADP 5 µm. Kata kunci: agregasi trombosit, DMT2, dislipidemia